# Square root 2 + square root 2/9? Please explain how to obtain the answer of 4 square root of 2 over 3

### 2 Answers | Add Yours

`sqrt2 + sqrt(2/9)`

Simplify the second term which can also be written as `sqrt2/sqrt9`

We know that the `sqrt9=3` or -3 but we do not need the -3 for this particular answer so will only solve using `sqrt9=3`

So we now have

`sqrt2 +sqrt2/3`

Now we need to find the common denominator (LCD) which is 3 So we multiply the first term by 3 in line with the LCD and as the second term already has the 3 we just leave as is or multiply by 1.

`sqrt2/1 times 3 +sqrt2/3 times 1`

= `(3sqrt2 + sqrt2)/3`

This can also be written as `(3sqrt2 +1sqrt2)/3`

Compare it to algebra. If it was 3x + x that would be 4x because we would add the two together. Apply the same principle to `3sqrt2 +1sqrt2` Thus:

= `(4sqrt2)/3`

`sqrt(2)+sqrt(2/9)=sqrt(2)+sqrt(2)/3`

`sqrt(2)(1+1/3)=(3+1)sqrt(2)/3=4sqrt(2)/3`